Crack Propagation in Linear Elasticity Based on the Concept of Material Forces - Brouzoulis, Jim (My University, 2007)
In fracture mechanics, we study the case of an existing crack in the material. In order to properly simulate the development of a crack, we need to model how fast and in what direction the crack grows in the case of propagation. In this thesis we have developed a framework for the simulation of crack propagation in linear elasticity based on the concept of material forces. Three different methods for propagating the crack has been investigated, (proportional propagation method, virtual crack extension and hybrid method). Two examples are presented. The first one is a plate with an inclined edge crack and the second one is a straight edge crack with circular holes. Both the plates are subjected to a prescribed displacement at the upper and lower boundary. From the simulations it is shown that the three propagation methods give very similar results. Further it is proposed that the proportional propagation method should be used, as it is the fastest of the three methods.
Keywords: Teknisk mekanik; Applied Mechanics